2009
DOI: 10.3892/ijo_00000487
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced des-γ-carboxy prothrombin production in hepatocellular carcinoma

Abstract: Abstract. Des-Á-carboxy prothrombin (DCP) is an established HCC tumor marker, but the precise mechanism of its production is still unclear. Recently, we demonstrated that cytoskeletal changes during epithelial-to-fibroblastoid conversion (EFC) or epithelial mesenchymal transition (EMT) induced by chemicals plays a critical mechanistic role in DCP production via impairment in vitamin K uptake. Our proposed mechanism of DCP production is consistent with substantial clinical evidence. Supplementary vitamin K2 ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 44 publications
3
38
0
1
Order By: Relevance
“…Second, various events that enhance the efficiency of cancer cell EMT predict cancer invasion, metastasis, and reduced survival in HCC patients. Third, circulating EMT markers are most elevated in HCC patients with metastatic cancer (29,30). The present study by Chen et al advances this field by demonstrating that CDH1L-ARHGEF9-Cdc42 signaling plays an important role in regulating liver cell EMT (4).…”
Section: Cirrhosis Emt and Hccmentioning
confidence: 71%
“…Second, various events that enhance the efficiency of cancer cell EMT predict cancer invasion, metastasis, and reduced survival in HCC patients. Third, circulating EMT markers are most elevated in HCC patients with metastatic cancer (29,30). The present study by Chen et al advances this field by demonstrating that CDH1L-ARHGEF9-Cdc42 signaling plays an important role in regulating liver cell EMT (4).…”
Section: Cirrhosis Emt and Hccmentioning
confidence: 71%
“…However, several molecules mediate the effect of HIF-1α in different cancers and its specific tumor-promoting mechanisms in HCC remain unclear. Murata et al showed that HIF-1α overexpression is associated with the production of an abnormal prothrombin, des-γ-carboxyl prothrombin or DCP, a known tumor marker in HCC [22], and HIF-1α promotes angiogenesis and metastasis via the upregulation of vascular endothelial growth factor (VEGF) and matrix metalloproteinases [23,24]. The effect of hypoxia on chemokines and their ligands was examined by Muller et al, who showed that the role of hypoxia in metastasis is mediated by its effect on the chemokine receptor CXCR4, which controls the metastatic homing of tumor cells to organs expressing high levels of its ligand SDF1 [25].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is involved in neo-angiogenesis and the formation of new blood vessels, induction of gene expression through the transcription factor Hif1α that regulates more than 50 targets genes and also hypoxia stimulates EMT in HCC [120] involving PI3 kinase/AKT signaling [121][122][123] .…”
Section: Hypoxia and Tumor Progressionmentioning
confidence: 99%